2020
DOI: 10.1002/jeab.582
|View full text |Cite
|
Sign up to set email alerts
|

The role of verbal behavior in the establishment of comparative relations

Abstract: Twelve college students received conditional discrimination training with nonarbitrary and arbitrary stimuli, and derived comparative and transformation of function tests with a think‐aloud condition across 2 experiments. Participants who failed these tests received remedial verbal operant training. Four control participants received verbal operant training alone. Across both experiments, only 1 participant passed the derived comparative test after conditional discrimination training. However, all participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Second, participant self‐report data have supported the occurrence of mediating behavior. Results of talk‐aloud procedures during equivalence tests suggested mediating responses such as tacting sample stimuli, tacting comparison stimuli, tacting relations among stimuli, tacting physical features of stimuli, and intraverbally relating stimuli with both experimenter‐ and participant‐generated names for stimuli (e.g., Diaz et al, 2020; Meyer et al, 2019). Participants in Miguel et al (2015) reported assigning novel names to stimuli, visually imagining stimuli, and self‐generating rules for relating stimuli without instructions to do so.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, participant self‐report data have supported the occurrence of mediating behavior. Results of talk‐aloud procedures during equivalence tests suggested mediating responses such as tacting sample stimuli, tacting comparison stimuli, tacting relations among stimuli, tacting physical features of stimuli, and intraverbally relating stimuli with both experimenter‐ and participant‐generated names for stimuli (e.g., Diaz et al, 2020; Meyer et al, 2019). Participants in Miguel et al (2015) reported assigning novel names to stimuli, visually imagining stimuli, and self‐generating rules for relating stimuli without instructions to do so.…”
mentioning
confidence: 99%
“…Alternatively, when mediating responses were disrupted, correct responding on matching tasks decreased (Clough et al, 2016; Lowenkron, 2006; Sundberg et al, 2018). Several studies have also found that training verbal operants (i.e., tacts and intraverbals) was sufficient to establish MTS performance consistent with equivalence (Diaz et al, 2020; Jennings & Miguel, 2017; Ma et al, 2016). These results are suggestive of the beneficial effects of mediation, but the necessity of these responses to establish equivalence has yet to be definitively shown (Randell & Remington, 1999).…”
mentioning
confidence: 99%
“…The current analysis supports previous claims (Meyer et al, 2019; Miguel et al, 2015; Miguel, 2018) that participants may be engaging in verbal behavior while solving analogy tests, and that the product of their verbal responses may serve as additional sources of stimulus control. Although previous analogical reasoning studies often used typically developing adults as participants (Barnes et al, 1997; Barnes‐Holmes et al, 2005; Carpentier et al, 2003; Carpentier et al, 2004; Lipkens & Hayes, 2009), few report on participants' verbal responses, even though they may likely be tacting and intraverbally relating stimuli (Diaz et al, 2020; Santos et al, 2015). Skinner (1984) stated that problem solving may include verbal responses (speaker behavior) that generate discriminative stimuli to which the individual can respond (listener behavior), until a solution is reached.…”
Section: Discussionmentioning
confidence: 99%
“…"Accurate" relational responses are often produced after a sequence of precurrent behavior. Therefore, trials in relevant experiments or circumstances in which relational responding might occur, may meet the definition of a "problem," with the relational response being the outcome of successful problem solving (Diaz et al, 2020;Miguel, 2018;Moustakis & Mellon, 2018;Palmer, 2004). Explaining problem solving with another specific type of problem solving (i.e., relational responding) may represent a valid higher-order explanation, but the extent to which this type of analysis is useful, in particular in the absence of an explanation for the problem solving that occurs in the process of relational responding, is unclear to us.…”
Section: Problem Solvingmentioning
confidence: 99%